2014
DOI: 10.1002/2013ja018870
|View full text |Cite
|
Sign up to set email alerts
|

Wave activity at ionospheric heights above the Andes Mountains detected from FORMOSAT‐3/COSMIC GPS radio occultation data

Abstract: An estimation of the ionospheric wave activity, derived from 4 years of FORMOSAT-3/ COSMIC GPS (Taiwan's Formosa Satellite Mission 3/Constellation Observing System for Meteorology-Global Positioning System) radio occultation electron density data, is presented. A systematic enhancement at the eastern side of the Andes range with respect to the western side is observed. A fitting method to remove the wavelike component from each measured profile and estimate the wave activity is described. The differential effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…They observed a small region of positive zonal GW momentum flux at 50 • S, 75 • W in an altitude of 30 km. A large eastward GW momentum flux during local winter has been observed by de Wit et al (2017) using SAAMER (Southern Argentina Agile Meteor Radar; 53.7 • S, 67.7 • W) and they explain this with secondary GWs due to stratospheric sources over the Andes mountains in connection with large-amplitude mountain waves breaking in the weak stratospheric winds.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…They observed a small region of positive zonal GW momentum flux at 50 • S, 75 • W in an altitude of 30 km. A large eastward GW momentum flux during local winter has been observed by de Wit et al (2017) using SAAMER (Southern Argentina Agile Meteor Radar; 53.7 • S, 67.7 • W) and they explain this with secondary GWs due to stratospheric sources over the Andes mountains in connection with large-amplitude mountain waves breaking in the weak stratospheric winds.…”
Section: Discussionmentioning
confidence: 92%
“…Alexander et al, 2010;Geller et al, 2013). Further enhancement is visible east of the Andes and above all around the Antarctic Peninsula as has been reported, for example, by de la Torre et al (2012) and Hindley et al (2015). In the following we will refer to the run using zonal mean GW weights according to Fig.…”
Section: Stratospheric Gw Fields and Experimental Setupmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been long known that the thermosphere is routinely disturbed by gravity waves (GWs) propagating from below. In some cases, the sources of strong wave activity in the thermosphere-ionosphere can be traced back to various phenomena in the troposphere, like severe storms (Hung et al, 1979), tsunami (Artru et al, 2005;Garcia et al, 2014;Hickey, 2011), deep convection (Miller et al, 2015), or flow over mountains (de la Torre et al, 2014). Modeling studies have demonstrated that GWs of various scales excited in the troposphere can effectively propagate to the upper thermosphere surviving filtering in the middle atmosphere and damping by exponentially growing with height molecular diffusion and thermal conduction (e.g., Fritts & Lund, 2011;Gavrilov & Kshevetskii, 2013;Heale et al, 2014;).…”
Section: Introductionmentioning
confidence: 99%